Centrifugal instability of Stokes layers in crossflow: The case of a forced cylinder wake - D'adamo, Juan Gastón Leonel (2015)
The wake flow around a circular cylinder at Re ≈ 100 performing rotatory oscillations has been thoroughly discussed in the literature, mostly focusing on the modifications to the natural Bénard-von Kármán vortex street that result from the forced shedding modes locked to the rotatory oscillation frequency. The usual experimental and theoretical frameworks at these Reynolds numbers are quasi-two-dimensional, because the secondary instabilities bringing a three-dimensional structure to the cylinder wake flow occur only at higher Reynolds numbers. In this paper, we show that a three-dimensional structure can appear below the usual three-dimensionalization threshold, when forcing with frequencies lower than the natural vortex shedding frequency, at high amplitudes, as a result of a previously unreported mechanism: a pulsed centrifugal instability of the oscillating Stokes layer at the wall of the cylinder. The present numerical investigation lets us in this way propose a physical explanation for the turbulence-like features reported in the recent experimental study by the present authors.